2015
DOI: 10.15430/jcp.2015.20.4.260
|View full text |Cite
|
Sign up to set email alerts
|

Adequate Dextran Sodium Sulfate-induced Colitis Model in Mice and Effective Outcome Measurement Method

Abstract: Background:Dextran sodium sulfate (DSS)-induced colitis mouse model is used for research of inflammatory bowel disease. The aim of this study was to establish the adequate conditions for DSS mice model, and to find useful tool to measure inflammation.Methods:The 2.5% DSS was administered to six male C57BL/6 mice and 4% DSS to eight mice at 5 or 9 weeks of age. Each group was consisted of 6 mice with control group in which vehicle was administered instead of DSS. The mice were sacrificed on the 7th day after DS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
58
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(68 citation statements)
references
References 27 publications
9
58
0
1
Order By: Relevance
“…Our data contradicts the previous report[ 9 ], in which animals started to improve clinically and histologically after DSS withdrawal. These differences between studies may reflect the influence of the microbiome and/or the animals’ age, as previously reported in experimental DSS colitis[ 27 , 28 ]. In addition, it has been reported that UC patients in clinical and endoscopic based remission presenting with active histological inflammation possess a higher risk for clinical relapse[ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 92%
“…Our data contradicts the previous report[ 9 ], in which animals started to improve clinically and histologically after DSS withdrawal. These differences between studies may reflect the influence of the microbiome and/or the animals’ age, as previously reported in experimental DSS colitis[ 27 , 28 ]. In addition, it has been reported that UC patients in clinical and endoscopic based remission presenting with active histological inflammation possess a higher risk for clinical relapse[ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 92%
“…A). Colon length decreases during DSS‐induced colitis and is a measure of disease severity . On day 7, mice were euthanized and the length of harvested colon tissue was measured.…”
Section: Resultsmentioning
confidence: 99%
“…Colon length decreases during DSS-induced colitis and is a measure of disease severity. 49 To determine if the level of inflammatory cytokines was increased in colon tissue homogenates after DSS treatment, inflammatory cytokines in mice colon tissue homogenates were assayed by ELISA ( Fig. 1D).…”
Section: Malt1 −/− Mice Are More Susceptible To Dss-induced Colitis Tmentioning
confidence: 99%
“…Mice were sacrificed and distal colon, mesenteric fat, and blood were collected for RNA, histology, bacterial culture assay, and toxin analysis. Histological scores were measured as previously described (49)(50)(51).…”
Section: Methodsmentioning
confidence: 99%